ANALISIS DAYA TAMPUNG BEBAN PENCEMARAN DETERJEN AIR SUNGAI SANUA KELURAHAN SANUA KECAMATAN KENDARI BARAT - La Ode Siwi; La Ode Midi; La Ode Muhammad Erif; Inka Dwiyanti (Jurnal Ecogreen, 2019)
Water is part of the environment has an important function for human life and other living things. The level of water pollution has increased significantly followed by an increase in population. Water pollution is caused by several things, one of which is detergent waste. This study aims to determine the concentration of detergents as well as the load capacity of sanua river water detergent pollutants, in Sanua Village, West Kendari District, Kendari City.The results showed that the type of detergent used by the public was powder detergent which contained LAS (Linear Alkylbenzene Sulfonate) compounds. Detergent concentration analysis results showed that, detergent concentration in February, station 1 was 0.067µg l -1, station 2 was 0.106µg l-1, station 3 was 0.117µg l-1, station 4 was 0.129µg-1, station 5 was 0.112 μg-1 and station 6 were 0.109 μg l-1. Whereas in March station 1 was 0.128µg-1, station 2 was 0.496µg l -1, station 3 was 0.139µg l-1, station 4 was 0.107µgl-1, station 5 was 0.265µg l-1 and station 6 was 0.149µg l-1 1 The average concentration of the pollution load capacity of detergents is 0.106 µg-1 in February and 0.215 µg l-1 in March, this value is far from the quality standard stipulated by PP. No. 82 of 2001, where the quality standard is 200 µg l-1 for grades 1-3.